A benchmarking implementation framework for automotive manufacturing SMEs - Md. Deros, Baba; Yusof, Sha'ri Mohd.; Md. Salleh, Azhari (Emerald Group Publishing Limited, 2006)
Purpose: The purpose of this paper is to present a conceptual framework for benchmarking implementation in small medium-sized enterprises (SMEs) taking into consideration their characteristics. Design/methodology/approach – The paper begins with the review on the definition of SME and a comparison of the characteristics of SMEs and large organizations. It presents the need for a framework and its relationship with benchmarking and TQM. This is followed by reviewing the benchmarking implementation frameworks proposed by researchers and discusses these frameworks based on their strengths and weaknesses from SMEs perspective. The frameworks were categorised into two broad types based on the different writer's background and the approach on how they view the benchmarking implementation process. Findings – The paper suggested a conceptual framework for benchmarking implementation dedicated to the automotive manufacturing SMEs. This framework guides them through from the start to end of the benchmarking process. The framework was validated at six pilot case study companies, which gave useful comments and suggestions regarding the usefulness and applicability within the SMEs context. Research limitations/implications – The conceptual framework is still in the development stage and research is undertaken to include the pilot study companies suggestions and comments into the final version of the framework. Practical implications – This guidance and framework provides a useful guide for companies to adopt and adapt before embarking on their benchmarking journey. Originality/value – This paper fulfils an identified knowledge gap and offers practical help to SMEs starting out a benchmarking implementation effort.